In vitro antisense activity of chitosan/AsODN complexes - Enneli, Burcu; Özabaş Turan, S.; Uslu, B.; Akbuğa, J. (İstanbul Kültür Üniversitesi, 2009)
In this study, the complex forms of AsODNs (phosphodiester and phosphorothioate forms) were prepared by using a cationic polymer called chitosan. The effect of chitosan mol wts and chitosan/AsODN ratio on the complex properties was studied. Afterwards, the physicochemical properties such as zeta-potential and particle size of complexes were measured and the in vitro antisense activities of the appropriate formulations were investigated. Full complexation was observed with phosphorothioate AsODN at the ratio of 10:1 (+/-), however phosphodiester AsODN could not be formed full complex with chitosan. The antisense activity of 100:1 (chitosan/AsODN) complexes which have approximately 200 nm particle size, was measured based on the inhibition of β-galactosidase by the antisense containing formulations into the b-Gal transfected HeLa cell lines. Eventually, both of these complex forms protected AsODNs from potential enzymatic degradations. In 100:1 (+/-) complex formulations, high antisense activity (88- 90%) was observed. As a result, chitosan can be considered as a suitable carrier especially for phosphorothioate modified AsODNs. Molecular weight of chitosan and chitosan/AsODN mass ratio had no importance in in vitro inhibition. This study can form the basis for the forthcoming studies related with carrier systems of AsODNs that will be done with chitosan polymer
Keywords: Antisense oligonucleotide; chitosan; complex; carrier; gene expression